From bark to bench: innovations in QS-21 adjuvant characterization and manufacturing - Talukdar, Priyanka; Winegar, Peter H.; Hudson, Graham A.; Astolfi, Maria C. T.; Inman, Jamie L.; Keasling, Jay D.; Mukundan, Harshini (Frontiers in Immunology, 2025)
Adjuvants enhance immune responses; thereby increasing the efficacy of vaccines and longevity of the immune response. Despite this critical role, discovery of new adjuvants and pipelines to immunologically characterize and produce them at scale remain inefficient. In this review, we examine key challenges in the development of adjuvants and discuss emerging technological solutions using the saponin-based adjuvant, QS-21, as a central case study. QS-21 is a potent immunostimulant that promotes both humoral and cellular immunity and is a component of several FDA-approved adjuvant systems. In this manuscript, we review current understanding of the cellular and molecular mechanisms of QS-21 action, including interaction with antigen-presenting cells and role in inflammasome activation and T cell polarization. Despite its efficacy, factors such as hydrolytic instability, dose-limiting toxicity, and dependence on ecologically sensitive natural sources constrain broader application of this adjuvant. We discuss strategies to improve QS-21 function and delivery, including structural modification, combination with complementary immunostimulants, and formulation in nanoparticle-based systems; and address advances in synthetic biology and bioengineering that offer promise towards sustainable production of QS-21 and its analogs in microbial and plant-based platforms. Finally, we propose a vision for an integrated adjuvant development pipeline—from bark to bench—that leverages synthetic biology, artificial intelligence, and systematic immuno-profiling in order to accelerate discovery and deployment of next-generation adjuvants. Together, this review provides strategies to integrate and innovatively deploy emerging technologies in order to enable rapid discovery, development and deployment of known and new-to-nature adjuvants for health applications.